Answer:
[tex]\mathrm{The\:solutions\:to\:the\:system\:of\:equations\:are:}[/tex]
[tex]x=3,\:y=-1[/tex]
Step-by-step explanation:
[tex]3x - 4y = 13[/tex]
[tex]5x + 4y = 11[/tex]
isolate x for 3x-4y=13
[tex]\mathrm{Subsititute\:}x=\frac{13+4y}{3}[/tex]
[tex]\begin{bmatrix}5\cdot \frac{13+4y}{3}+4y=11\end{bmatrix}[/tex]
[tex]\frac{65+32y}{3}=11[/tex]
now isolate y for [tex]\frac{65+32y}{3}=11[/tex]
[tex]\frac{65+32y}{3}=11[/tex]
[tex]65+32y=33[/tex]
[tex]32y=-32[/tex]
Divide both sides by 32
[tex]\frac{32y}{32}=\frac{-32}{32}[/tex]
[tex]y=-1[/tex]
[tex]\mathrm{For\:}x=\frac{13+4y}{3}[/tex]
[tex]\mathrm{Subsititute\:}y=-1[/tex]
[tex]x=\frac{13+4\left(-1\right)}{3}[/tex]
[tex]=\frac{13-4\cdot \:1}{3}[/tex]
[tex]=\frac{9}{3}[/tex]
[tex]\mathrm{Divide\:the\:numbers:}\:\frac{9}{3}=3[/tex]
[tex]=3[/tex]
[tex]\mathrm{The\:solutions\:to\:the\:system\:of\:equations\:are:}[/tex]
[tex]x=3,\:y=-1[/tex]